Rumpon Atraktor Ijuk: Teknologi Alat Bantu Penangkapan Ikan untuk Nelayan Kabupaten Nagan Raya, Provinsi Aceh - Hafinuddin Hafinuddin; Edwarsyah Edwarsyah; Muhammad Rizal (Universitas Teuku Umar, 2018)
Traditional fish aggregating devices (FADs) as fishing aids for surface gill net to catch pelagic fish were used by fishery community partner at Kuala Pesisir Sub District Nagan Raya District, so that operational/maintenance is high cost and those incomes of gill net’s fishermen obtains small. Therefore, palm fiber FADs technology is expected to alternatively increase income of surface gill net fishermen. Education, training, and accompaniment is approached to accomplish fishermen problems. Community partnership programe (PKM) was conducted in March until November 2018. Community partnership programe has increased knowledge and skill for fishery community. In addition, the quality of palm fiber FADs technology is better than the traditional FADs and production of fish catching.